Institutionalising the experience capitalization approach: from theory to practice - Ouattara, Haoua (Technical Centre for Agricultural and Rural Cooperation, 2019)
During 2018 and following the workshops organised by CTA, the Oxfam offices in Burkina Faso decided to institutionalise the experience capitalization approach. This is now included in the organisation's operational plan and also in its new project proposals. Oxfam plans to operationalise its monitoring, evaluation, accountability and learning platform to boost the use of the capitalization approach, and involve other Oxfam offices in other countries in West Africa